Application for Revision of the Judgment of 11 July 1996 in the Case concerning Application of the Convention on the Prevention and Punishment of the Crime of Genocide (Bosnia and Herzegovina v. Yugoslavia). (2014) - Unknown
Abstract : 1 International Court of Justice — Jurisdiction — Finality of judgments — Revision — Statute of the International Court of Justice, Article 61 — Requirement of newly discovered facts — Whether facts must have existed at the time of the judgment in respect of which revision sought — Subsequent facts — Federal Republic of Yugoslavia ("FRY") — 1996 Judgment upholding jurisdiction under the Convention on the Prevention and Punishment of the Crime of Genocide, 1948 — Subsequent admission of FRY as Member State of the United Nations — Whether implying FRY was not party to Statute or Genocide Convention at time of 1996 Judgment — Whether new facts within the meaning of Article 61 State succession — Succession and continuity of States — Socialist Federal Republic of Yugoslavia — Whether FRY the continuation of the former Yugoslavia — Membership of the United Nations — Participation in treaties — Convention on the Prevention and Punishment of the Crime of Genocide, 1948 International Organizations — United Nations — Membership — Yugoslavia — Status of Yugoslavia between 1992 and 2000 — Whether Member of the United Nations — Whether party to the Statute of the International Court of Justice — Whether bound by Convention on the Prevention and Punishment of the Crime of Genocide, 1948